Investigation of 9th Grade High School Students’ Attitudes towards Science Course - Orhan Karamustafaoğlu; Adem Bayar (International Journal of Assessment Tools in Education)
In this study, ninth grade students’ attitudestowards science were investigated in terms of self-regulation strategies,motivational beliefs and gender variables. The sample of this study includes322 male and 296 female in total 618 students from 3 different high schools(Science high school, Anatolian high school, and Vocational high school) incenter district of Amasya city. To collect the data, the researchers employed“Motivated Strategies for Learning Questionnaire” which has been developed byPintrich and De Groot in 1990, adapted into Turkish by Uredi in 2005 andconsists of 44 items and “Colorado Learning Attitudes about Science Survey(CLASS)” has been developed by Adams and others in 2006, adapted into Turkishby Bayar and Karamustafaoğlu in 2015 and consists of 36 items. For dataanalysis, mean, standard deviation, independent t-test and correlation wereaddressed. The results of this study show that there are statisticallysignificant relationships between 9th grade students’ attitudestowards science and self-regulation strategies, motivational beliefs, andgender.